Digital Financial Literacy and AI-Driven Digital Finance Adoption: The Mediating Role of Customer Value Proposition in the Banking Industry in Cameroon - Takemeyang, Ayuk; Ketuma, Henry Jong; Akpor, Tambi Andison (Law and Economy, 2025)
The rapid integration of artificial intelligence (AI) in digital finance has transformed the banking landscape, necessitating a deeper understanding of the factors influencing its adoption. This study investigates the effect of digital financial literacy on customers’ intention to adopt AI-driven digital finance, with customer value proposition (CVP) serving as a mediating variable. Surveys were employed to collect data from 466 banking customers in Cameroon, which were analyzed using partial least squares-based structural equation modeling (PLS-SEM). It was revealed that DFL influences CVP, including Functional, Benefit, Symbolic and Emotional Value, which are involved in the intention to use digital finance. The mediation of the nexus between DFL and the intention to use digital finance was carried out using the four dimensions of CVP. Theoretical and practical insights into the development of digital finance services in a developing country are provided by this study’s findings. Theoretically, the research on drivers of the customer value proposition in financial services is extended. As practical implications, financial institutions are advised to focus on emotional and symbolic values such as brand image, customer experience, and trust. It is also recommended that the government and institutions continue activities that promote digital financial literacy.